Motivations, emotions and satisfaction: the keys to a tourism destination choice - Pestana, M.H.; Parreira, A.; Moutinho, L. (Journal of Destination Marketing and Management, 2020)
A noticeable void remains in the appreciation of what motivates the senior tourism market. This study aims to contribute to the advancement of knowledge in the field of tourism consumer psychology by improving the existing understanding of the motivation and related psychological processes that underly intentions and decision-making in respect of tourist destinations. A model explaining the mediation role played by satisfaction in the relationship between motivation, emotion, and behavioural intentions is developed. A sample of 460 seniors visiting Lisbon is used, and through the application of structural equation modelling to the data obtained, it is found that satisfaction mediates the relationship between motivations and emotions, and behavioural intentions, simultaneously strengthening the positive association between push and pull motivations. Seniors’ previous experience is seen to moderate the positive effect of satisfaction on intention. Additionally, there is support for motivational differences, which have a significant impact on behavioural intentions, between younger (55–60 years) and older seniors (> 60 years). Finally, several academic and managerial implications are outlined, including the usefulness of the model developed in different geographical settings.